Calidad del agua de consumo humano en el sistema de abastecimiento de agua potable en la parroquia Siete de Octubre, del Cantón Quevedo, Provincia de Los Ríos. - Lopez Ortega, Oscar Fabricio (2016)
The present research project consisted in evaluating the quality of water for human consumption in the process of capture, treatment, distribution and consumption in the parish 7 de Octubre Quevedo province of Los Ríos, in the year 2017. The state was evaluated The different phases of the drinking water supply system through direct observation, an interview applied to the head of the city's drinking water plant that showed that only the chlorine gas is collected in the collection, the water distributed was also checked with the perception Citizen on the quality of the service applying a survey, which showed that the water received has an odor, flavor, color and solids dissolved as sand. The physicochemical and microbiological characterization of the quality of water for human consumption in the stages of abstraction, distribution and consumption allowed to establish the quality of water by comparing the results with the Environmental Quality norms and discharge of effluents Water Resources, WHO and Norms INEN 1108 (2011): Drinking water denoting non-compliance with established standards for physicochemical parameters such as apparent color, turbidity, total dissolved solids, manganese, iron, residual chlorine. In addition, the Water Quality Indexes were applied; Such as the GWQI, NSF and Dinius; Which certified that in catchment with the GWQI was obtained a value of 72.255 that according to the classification is a poor water for human consumption, in the consumption phase was applied the NSF whose values were 72-86 being of good quality for consumption, in Dinius were given values of 85-91 having a nomenclature of a minor treatment required. With the results obtained a proposal of a Manual of Good Practices for the adequate domestic use of water for the human consumption in the Venus parish of the river Quevedo of the Canton Quevedo was elaborated; Areas of use were identified, such as kitchen, bathroom, laundry, gardening, street irrigation, elevated tanks and floor cleaning. The risk points were determined as well as waste of water and pollution where the kitchen, bathroom and laundry stand out with greater waste. Control measures were established for each area.